Rainfall‐Induced Runoff from Exposed Streambed Sediments: An Important Source of Water Pollution. Issue 1 (1st January 2015) - Frey, S. K.; Gottschall, N.; Wilkes, G.; Grégoire, D.S.; Topp, E.; Pintar, K. D. M.; Sunohara, M.; Marti, R.; Lapen, D. R.
Abstract : When surface water levels decline, exposed streambed sediments can be mobilized and washed into the water course when subjected to erosive rainfall. In this study, rainfall simulations were conducted over exposed sediments along stream banks at four distinct locations in an agriculturally dominated river basin with the objective of quantifying the potential for contaminant loading from these often overlooked runoff source areas. At each location, simulations were performed at three different sites. Nitrogen, phosphorus, sediment, fecal indicator bacteria, pathogenic bacteria, and microbial source tracking (MST) markers were examined in both prerainfall sediments and rainfall‐induced runoff water. Runoff generation and sediment mobilization occurred quickly (10–150 s) after rainfall initiation. Temporal trends in runoff concentrations were highly variable within and between locations. Total runoff event loads were considered large for many pollutants considered. For instance, the maximum observed total phosphorus runoff load was on the order of 1.5 kg ha −1 . Results also demonstrate that runoff from exposed sediments can be a source of pathogenic bacteria. Campylobacter spp. and Salmonella spp. were present in runoff from one and three locations, respectively. Ruminant MST markers were also present in runoff from two locations, one of which hosted pasturing cattle with stream access. Overall, this study demonstrated that rainfall‐induced runoff from exposed streambed sediments can be an important source of surface water pollution.